The Impact of Non-Fungible Tokens (NFT) Technology on the Art Industry - Blount, Austin; Dvouletý, Ondřej; Bočková, Nina, 1971-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2024)
This Bachelor’s Thesis explores the impact of Non-Fungible Tokens (NFTs) on the traditional art market, focusing on the Czech art industry. The study investigates the operational efficiencies, economic outcomes, and artist representation enabled by NFT adoption, alongside the regulatory and market dynamics involved. Employing a quantitative research approach, data was collected through surveys distributed to art industry stakeholders, including curators, art dealers, and galleries. The results highlight the role of NFTs in improving provenance tracking, artist visibility, and global market access, while also identifying challenges such as regulatory inconsistencies and adoption barriers. The survey took place in Prague, between the 5th and 10th of December 2024. The targeted sample were a combination of 37 professionals working in the art industry; artists represented by galleries; gallery managers; gallery curators; gallery owners and administrators. These findings provide actionable insights for stakeholders and contribute to academic discourse on blockchain applications in creative industries.
Vedoucí práce: Ondřej Dvouletý
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses